Pengembangan Aplikasi Inventory menggunakan Algoritma Differential Evolution dan C 4.5 berbasis Web - Rizal, Moch Miftakhul; Chulkamdi, Mukh. Taofik; Febrinita, Filda (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2025)
The main issue in Kepinos Warehouse lies in inefficient stock management, characterized by frequent cases of overstock, understock, and inaccurate record-keeping that disrupt operational performance. This study aims to develop a web-based inventory system integrating the Differential Evolution (DE) algorithm for stock optimization and the C4.5 algorithm for item category classification based on sales frequency. The system was developed using the Rapid Application Development (RAD) methodology to ensure iterative and user-centered design. System testing was conducted using Black Box Testing to verify functionality and Closed Beta Testing to evaluate user feasibility. The results show that all features performed as expected, with user validation scores of 74% from IT experts, 86.4% from warehouse administrators, and 76% from operational staff. These findings indicate that the system is technically and functionally feasible, enhancing efficiency, accuracy, and responsiveness in warehouse inventory management. Keywords: Inventory System, Differential Evolution, C4.5, Stock Optimation, RAD